Effect of weight control via dietary calorie restriction and treadmill exercise on lipid profile and overall gene and protein expression in mouse skin tissues - Jiang, Yu (Kansas State University, 2008)
Weight control via dietary caloric restriction and/or exercise has been demonstrated for cancer prevention. However, the underlying mechanisms are not clear. Previous studies in our lab showed that IGF-1 and IGF-1-dependent signaling were reduced by weight control. To confirm the requirement of IGF-1 reduction for cancer prevention, we restored IGF-1 in the exercised mice, which partially reversed the reduction of TPA-induced PI3K expression and PI3K-related 38:4 PI substrate. To explore the overall mechanistic impact, we further studied the effect of weight control on the profiles of lipid, gene and protein expression in TPA treated skin tissues. The mice were randomly assigned into 4 groups: ad libitum-fed sedentary control (control), ad libitum-fed exercise (AL+Exe), exercise but pair-fed at the amount of control (PF+Exe), and 20% of dietary calorie restriction (DCR). At the end of 10 weeks, the mice were treated with TPA topically for two hours. The body weights were significantly reduced in DCR and PF+Exe but not AL+Exe mice when compared with the control. Plasma and skin tissue triacylglycerides were significantly decreased in PF+Exe and DCR groups but not AL+Exe. Similar impact was found for the diacylglyceride profile in both plasma and skin tissue accordingly. Using Affymetrix microarray, 784, 223, and 152 probe sets were respectively found significantly changed by DCR, PF+Exe, and AL+Exe. PF+Exe and DCR showed similar impact on signaling pathways-related gene expression as analyzed by GenMAPP. Of the total 86 proteins identified by 2D-DIGE proteomics, 20 proteins were significantly changed by DCR. Overall, our results showed weight control via DCR or pair-fed exercise rather than exercise with ad libitum feeding significantly reduced body weight and body fat, resulting in reduction of IGF-1 and IGF-1-induced signaling such as PI3K and PI-related pathway. The overall impact upon lipid profiling and gene and protein expression by weight loss suggests many other mechanistic targets. Although we could not ambitiously clarify all the changes were related to anticancer mechanisms in the scope of this study, understanding of the relationship between weight control and TPA-induced skin cancer risk as well as IGF-1-dependent signaling pathways may reveal intrinsic mechanisms and provide novel approaches to prevent cancer in the future studies.
Keywords: Weight control; cancer prevention; Dietary calorie restriction; exercise; Health Sciences, Nutrition (0570)